THE IMPACT OF BOARD OF DIRECTOR’S DIVERSITY ON FINANCIAL PERFORMANCE AMONG BANKING COMPANIES LISTED ON IDX - Kurniawati, Herni; Sriwati , Sriwati (Graduate Program of Universitas Tarumanagara, 2023)
The current study investigates empirically how the diversity present in Indonesia's banking industry can enhance banking employment. The key participant categories that are discussed in this essay are gender, nationality, educational background, and age. This research uses a descriptive quantitative approach design because this research uses banking annual report data from the IDX website and firm’s website. For the 2018–2021 timeframe, the population of banking companies listed on the Indonesia Stock Exchange was used in this study. The research sample was selected using a purposive sampling technique with predetermined criteria. This study has shown that diversity on Indonesian banking boards of directors can significantly improve banking performance. By demonstrating how the board of directors' diversity regarding nationality, educational background, and age may greatly enhance banking performance. But not with gender diversity, which gives results that cannot improve banking performance in Indonesia.